Seismic Analysis of Flat Slab Structure Using ETABS Software - Awasthi, Aayush; Satbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2023)
Civil Engineers are facing a great challenge in structural designing. The design must fulfil various parameters which include economical structure, durability and serviceability. But taking these points in mind it becomes very difficult for an Engineer to fulfil all these requirements at a time when a design is performed manually. This digital tool used in civil engineering and comparing their results by taking in mind the requirements of the above points. In this research process a building is taken for analysis and design on well-known Software ETABS. Due to the freedom of space design, quicker construction time, architectural functionality, and economic factors, flat-slab building designs have significant advantages over typical slab-beam-column systems. The lack of deep beams and shear walls makes flat-slab structural systems far more flexible for lateral stresses than standard RC frame systems, which increases the system’s susceptibility to seismic occurrences. The critical moment in design of these systems is the slab-column connection, i.e., the shear force in the slab at the connection, which should retain its bearing capacity even at maximal displacements. In this study we are comparing a G+10 High rise building frame considering three different slab conditions i.e. conventional slab, flat slab and flat slab with staggered beams. For analysis we are utilizing analysis tool etabs.